From environmental to comprehensive security - Westing, Arthur H. (SpringerBriefs on Pioneers in Science and Practice, 2013)
This work presents the evolution of the traditional concept of "national security" as military security to additionally embrace "environmental security" and then necessarily also "social (societal) security", thence to be termed "comprehensive human security". It accomplishes this primarily by presenting 11 of the author's own benchmark papers published between 1983 and 2010 (additionally providing bibliographic citations to a further 36 of the author's related publications during that period). The work stresses the importance of transfrontier (regional) cooperation, and also recognizes global overpopulation as a key impediment to achieving comprehensive human security.